Patellofemoral Pain: A Not So Trivial Knee Injury (A Case Report) - Rashid, Aneesa Abdul; Devaraj, Navin Kumar; Kahar, Johan Abdul (International Journal of Human and Health Sciences (IJHHS), 2019)
Knee injuries are very common in sports, ranging from trivial knee strains to severe ligament, tendon and/or meniscus tear, knee joint fracture or dislocations. The treatment ranges from the basic rest, ice, compression and elevation (RICE) approach to oral medications and/or surgery. It usually entails some form of physiotherapy especially during the post injury period and with functional loss of motion or stiffness. For the professional sportsman, rehabilitation tends to be more intensive due to pressure to return to the sport as soon as possible. This case report will look at a-not-so-trivial knee injury diagnosed as patellofemoral pain syndrome (PFPS) in a 28 year old recreational athlete International Journal of Human and Health Sciences Vol. 03 No. 02 April’19. Page: 120-122